NavotaAs Community Center building the capacity of Navoteños towards sustainability - Shi, Shirley H. (College of Architecture, University of the Philippines Diliman, 2018)
The NavotaAs Community Center is a project that aims to help uplift the lives of Navoteños and give them a sense of identity and at the same time introducing and promoting the city. It is a center where the locals can learn skills to help alleviate them for alternative livelihood and additional source of income. The facilities will not be use only for training and lecture but also as incubator to maximize the use of the center. In line with that, retail spaces will be provided for the selling of products. There will also be a restaurant highlighting seafood and specialty shops sowcasing the city's OBOP (fish products). Congregation and open spaces are also provided for events, seminars, activities and others.